2020
DOI: 10.1016/j.isci.2020.101218
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable Chemicals Manufacturing Paradigm Using CO2 and Renewable H2

Abstract: The chemical industry must decarbonize to align with UN Sustainable Development Goals. A shift toward circular economies makes CO 2 an attractive feedstock for producing chemicals, provided renewable H 2 is available through technologies such as supercritical water (scH 2 O) gasification. Furthermore, high carbon and energy efficiency is paramount to favorable techno-economics, which poses a challenge to chemo-catalysis. This study demonstrates continuous gas fermentation of CO 2 and H 2 by the cell factory, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…DASware® control software was used for automated control of DO, temperature, and pH. The preculture was prepared and fermentation was performed as described previously ( Bommareddy et al, 2020 ) with some modifications. Briefly, The first seed culture was grown overnight at 30 °C with 200 rpm shaking in 10 mL of LB from a single colony.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DASware® control software was used for automated control of DO, temperature, and pH. The preculture was prepared and fermentation was performed as described previously ( Bommareddy et al, 2020 ) with some modifications. Briefly, The first seed culture was grown overnight at 30 °C with 200 rpm shaking in 10 mL of LB from a single colony.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the gasification of plant's waste, which allows the complete utilisation of carbon contained within the biomass, CO 2 , suitable for gas fermentation, can be captured from chemical plants and steel mills reducing its emission to limit the climate change ( Liew et al, 2016 ). Considering these advantages, C. necator H16 has been engineered to produce a wide range of commodity chemicals including methyl ketones, alcohols, terpenes, and alka(e)nes ( Bommareddy et al, 2020 ; Chakravarty and Brigham, 2018 ; Crepin et al, 2016 ; Grousseau et al, 2014 ; Krieg et al, 2018 ; Lu et al, 2012 ; Müller et al, 2013 ) demonstrating its versatility and potential as an industrial chassis.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve IPA production from CO 2 , Garrigues et al designed a pressurized bioreactor to provide higher gas abundance and increase the gas transfer rate, with the IPA titer reaching as high as 3.5 g/L by gas fermentation [ 138 ]. Similarly, Bommareddy et al established a continuous autotrophic fermentation system and obtained 7.7 g/L IPA [ 139 ]. Recently, an MES system was set up by coupling C. necator strain Re2133/pEG12 and water-splitting system, resulting in the production of 216 mg/L IPA [ 25 ].…”
Section: Synthetic Biology Applications Of C Necator H16mentioning
confidence: 99%
“…It can be considered an emerging autotrophic production platform and has been explored by several metabolic engineering studies [6,8] for the production of value-added compounds such as isopropanol [9], 2-hydroxyisobutyric acid [10], methyl ketones [11], alkanes [12], α-humulene [13], isobutanol [14] and acetoin [15]. Moreover, the recent studies demonstrated that the energy e ciency of CO 2 xation via the CBB cycle can be improved and the product titers increased by optimizing the fermentation process and bioreactor design [16,17].…”
Section: Introductionmentioning
confidence: 99%